HYPERVISOR PERFORMANCE BASE CLOUD COMPUTING AT MULTI PLATFORM VIRTUAL MACHINE - Isminarti (P3M STMIK Profesional Makassar, 2013)
Hypervisor using binary translation to translate physical machines to virtual machines and take a long time for translate binary code. There are two hypervisor default in Proxmox VE 2.1 namely KVM with fullvirtualization and openVZ with operating system-level virtualization technique, both technique are used together, if this case running together in server hypervisor it means that execution will be running slow. This research will be overcome this problem by choose the best hypervisor so virtual machine still running well if there are many request from client in cloud service. This research using quantitative type of research with experimental and comparative methode because we compare two hypervisor and than make virtual machine experiment using some scenario with trial. This research result two methode that all researcher can be used to test hypervisor performance to get the best hypervisor that is KVM that have better performance than openVZ so this hypervisor suitable to implemented in cloud computing.